TINJAUAN HUKUM PIDANA DALAM PERWUJUDAN KEADILAN LINGKUNGAN - Reguna, Mosezs Sahat; Putra, Alif Arhanda (Universitas Borneo Tarakan, 2023)
AbstractThe environment is the most vital element on this planet, especially in fulfilling theneeds of human life. Therefore, the relationship between humans and theenvironment is inseparable. Humans grow and develop along with the surroundingenvironment. As a gift and grace from Allah swt. for mankind in general, andespecially for the Indonesian nation, the environment is a source of life that coversall aspects and materials. Law enforcement has a broad meaning because it includesaspects of prevention and prosecution, by conditions in Indonesia which involve theactive participation of government elements in increasing public legal awareness.Nonetheless, criminal law enforcement in the environmental sector has not achievedthe expected goals at this time. One of the causes of this failure is the lack ofsynchronization, coordination, consistency, and harmony in terms of culture,structure, and substance in the criminal justice system. Law enforcement as aprocess involves the application of discretion associated with decision-making thatis not strictly regulated by legal norms but involves elements of personal judgment.Therefore, it can be said that law enforcement does not only mean theimplementation of laws, although in Indonesia this tends to be the case, so the term